A model for ranking plant pests and diseases (FinnPRIO) - Hannunen, Salla; Heikkilä, Jaakko; Tuomola, Juha (European Association of Agricultural Economists (EAAE), 2014)
There are so many potential plant pests that all cannot be subjected to a full scale risk assessment. There is therefore a need for a faster and lighter risk assessment procedure. FinnPRIO prioritisation model estimates the risk of exotic plant pests for Finland. It follows the basic structure of risk assessment, i.e. it separately estimates the probabilities of entry, establishment and spread, and the likely impacts. The model also has a management section. The total score is calculated using the most likely figures, but also simulated using a PERT distribution, providing a scale of potential risk for each species.
Keywords: Maatalous - yleistä, maatalousekonomia,maatalousneuvonta, maaseudun kehittäminen; kasvintuhooja; risk assessment; spread; invasive species; plant pest; impact; vieraslajit; priorisointi; vaikutukset; leviäminen; riskinarviointi; epävarmuus